Effect of sleep loss on pain—New conceptual and mechanistic avenues - Kourbanova, Kamila; Alexandre, Chloe; Latremoliere, Alban (Frontiers in Neuroscience, 2022)
Sleep disturbances increase pain sensitivity in clinical and preclinical settings, but the precise mechanisms are unknown. This represents a major public health issue because of the growing sleep deficiency epidemic fueled by modern lifestyle. To understand the neural pathways at the intersection between sleep and pain processes, it is critical to determine the precise nature of the sleep disruptions that increase pain and the specific component of the pain response that is targeted. Here, we performed a review of the literature about sleep disturbances and pain sensitivity in humans and rodents by taking into consideration the targeted sleep stage (REMS, non–NREMS, or both), the amount of sleep lost, and the different types of sleep disruptions (partial or total sleep loss, duration, sleep fragmentation or interruptions), and how these differences might affect distinct components of the pain response. We discuss the possible mechanisms involved, including an increase in inflammatory processes, a loss of nociceptive inhibitory pathways, and a defect in the cognitive processing of noxious input.